If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.50b + 6 = 11 Reorder the terms: 6 + 0.50b = 11 Solving 6 + 0.50b = 11 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 0.50b = 11 + -6 Combine like terms: 6 + -6 = 0 0 + 0.50b = 11 + -6 0.50b = 11 + -6 Combine like terms: 11 + -6 = 5 0.50b = 5 Divide each side by '0.50'. b = 10 Simplifying b = 10
| 8-x=12-2x | | b=9b-24 | | 9y^2-33y+24= | | -9+2(4g-7)=9 | | x+4=9-2x | | m+4+5=22 | | 33=x+4 | | z=1+i^12 | | 14+4=x+5x | | -160+-52x+1x^2+x^3=0 | | 5x(3x+5)=0 | | k^3-18k-7k^2=0 | | (3s+20)(s+1)=-22 | | (3s+20)(s+1)=-20 | | 4x-8=5x-2 | | 9x+3=8x+19 | | p(p+1)=6 | | 2m^2-12m=2m-24 | | x^3-13x^2+36x=0 | | x+6=2x-8 | | 3x-5=x+3 | | 5m(5m+4)=-4 | | 2x^2-9x=26 | | 2x+6=19-3 | | 4x^2-21x=-5 | | 8x^2=-9x | | p^2=22p | | 2(2x+3)=4x-6 | | 5x+2=x+17 | | 10y-2=7+3y | | 8.4+x=-3.9 | | x-(-9)=-9 |